Modeling of Color TV-tube Shadow Mask Surface - Čepulis, V.; Navikas, D. (Elektronika ir Elektrotechnika, 2006)
There are presented two color TV-tube shadow mask surface modeling methods. Technique offered in this work is based on electron trajectory modeling in measured or modeled electric and magnetic fields, created by developed TV-tube. In order to reduce calculation duration electron trajectories deflection centers coordinates are approximated using power polynomial. Analysis of both methods systematic errors is presented. There are calculated electron trace shift on the screen influence coefficients of imprecise electron deflection to the defined point of the screen. Both methods can be used in TV-tube design stage. Ill.4, bibl.2 (in English; summaries in English, Russian and Lithuanian).